Lights out! - McNamara, Michael, 1953-; Holm, Judy; Suzuki, David T., 1936-; Canadian Broadcasting Corporation; Public Broadcasting Service (U.S.); PBS Distribution (Firm) ([Arlington, Virginia] : [PBS], 2015)
Joins leading scientists in the lab and in the field who are discovering how much harm light at night may be causing. Follows the ground-breaking steps being taken to protect humans from this environmental hazard.
Originally broadcast in 2012 as an episode of the CBC television series: The nature of things.
Directors of photography, Catherine Lutes, James Griffith ; editor, Roderick Deogrades ; music, Kurt Swinghammer.
Narrator, David Suzuki.
DVD; NTSC; region 1; widescreen presentation; stereo.
In English; with optional English subtitles.
104658
Keywords: Light -- Physiological effect; Lighting -- Physiological aspects; Light pollution; Educational television programs; Science television programs; Nonfiction television programs